Endophytic Bacteria in Acalypha indica L. Leaves and Their Antimicrobial Activity Against Staphylococcus aureus and Candida albicans - Syafitri, Aini; Fitri, Lenni; Suhartono, Suhartono (Molecular and Cellular Biomedical Sciences, 2025)
Background: The anting-anting plant (Acalypha indica L.) is used in herbal medicine in the treatment of various diseases. The leaf extract of this plant is known for its antimicrobial activity, but the antimicrobial properties of the endophytic bacteria within its leaves have never been reported. This research aims to determine the antimicrobial activity of endophytic bacteria from the leaves of the anting-anting plant. Materials and methods: The isolation of endophytic bacteria was performed using the spread plate method on nutrient agar (NA) media. Following isolation, the bacterial isolates were characterized through macroscopic and microscopic examination, as well as biochemical tests, which included indole production, hydrogen sulfide (H2S) production, motility, Simmons citrate utilization, methyl red-Voges-Proskauer (MR-VP) test, catalase test, and triple sugar iron agar (TSIA) test. Identification of the bacterial isolates was conducted according to Bergey's Manual of Systematic Bacteriology. Additionally, the antimicrobial activity of the isolates was assessed using the diffusion methodResults: Fourteen isolates of anting-anting leaf endophytic bacteria were obtained (coded as BEDA 1 to BEDA 14). The BEDA 5 isolate exhibited the largest inhibitory zone diameter against Staphylococcus aureus (31.48 mm), while BEDA 9 showed a significant inhibitory zone diameter against Candida albicans (17.84 mm). Conclusion: The two isolates (BEDA 5 and BEDA 9) exhibited significant antimicrobial activity, indicating their potential as promising candidates for alternative antimicrobial agents. These results suggest that endophytic bacteria from Acalypha indica may play an essential role in combating antibiotic resistance and in the development of new therapeutic strategies.Keywords: endophytic bacteria, characterization, antimicrobial activity, Acalypha indica